Blood Plasma Hormone Testosterone Level and Sperm Quails (Coturnix coturnix japonica) Quality caused by Lemuru Fish and Palm Oil - Fitriyah, A; Wihandoyo, Wihandoyo; Supadmo, Supadmo; Ismaya, Ismaya (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2008)
The research was conducted to know the effect of lemuru fish oil (LFO) and palm oil (PO) on blood plasma testosterone and sperms quality of quails (Coturnix coturnix japonica). The experiment used 15 male quails of 12 weeks of age. The birds were divided into 5 feeding treatments, which were; R-0 (control), R-1 (3% LFO), R-2 (6% LFO), R-3 (3% PO) and R-4 (6% PO). Data on testosterone level and semen quality (sperm motility, sperm morfology, sperm viability and sperm concentration) were analyzed quantitavely. Results showed that testosterone level of birds given 6% LFO was significantly higher than those given 6% PO (4.92 vs 2.44 ng/ml). Feeding birds with 6% LFO or 3% PO resulted in good quality of sperms as indicated by sperm motility (78.30 and 78.30%), viability (73.19 and 86.06%) and concentration (250.00 and 255.30 x109/ml). In conclusion, feeding quails with 6% LFO or 3% PO were able to increase level of testosterone, HDL, LDL and sperm quality. (Animal Production 10(3): 157-163 (2008) Key Words: Testosterone, sperm quality, lemuru fish oil, palm oil